Bangladesh: the importance of farmers’ seed systems and the roles of Community Seed Wealth Centers - Policy Research for Development Alternative (UBINIG, 2018)
This brief describes the most recent activities of UBINIG (Policy Research for Development Alternative) to support the the Nayakrishi Seed Network (NSN) of the Nayakrishi Andolon or New Agricultural Movement of Bangladesh, now active in three major agro-ecological zones of the country and bringing together 300,000 farmers. The NSN is made up of regional Community Seed Wealth Centers and Seed Huts at the village level. Seed Huts typically conserve multiple varieties of all important traditional crops including cereals, pulses, vegetables and spices. Women seed custodians play key roles in the NSN. Community Seed Wealth Centers provide back-up to Seed Huts, carry out strategic research and organize capacity building.